Konflik Agraria Di Kabupaten Pulau Morotai (Studi Peran Pemerintah Daerah Pada Konflik Pertanahan di Masyarakat) - Lesang, Indra; Qodir, Zuly (Journal of Governance and Public Policy, 2014)
Matter agrarian (matter land) is matter live and livelihood human, due to land is origin and source food. Land causeproblem and conflict. Land conflict case in Pulau Morotai regency is conflict land between five villagers with TNI-AU.This research use descriptive qualitative approach. Data source obtained from study literature, documentation, andinterview with some information sources. First result research, this conflict land matters have roots in from history.This land matters conflict development originating from from difference perception of mastery land. Less firm attitudeLocal Government also is one of this source conflict. The conflict by economy impact to community five village particularlyin development. All invenstor also afraid instill the capital, this was because because happened resistance bysociety five village. Second, less intense it Pemerintah Daerah Melakukan Konsiliasi, mediation. Conciliation and Mediasionly happened when action protest getting intense. Happened by house foundation demolition and community propertyhouse five village no intervene by government to block. Third, policies issued by government of Pulau Morotairegency in conflict land matters between community five Desa with TNI-AU not touched in society. Policies made toomuch bias elite.